(untitled) (Raparin Journal of Humanities (RJH), 2025)
This research highlights the scholar “Ibn Furak’s” book “Al-Hadith Problems” in the aspect of understanding the text of the hadith and its jurisprudence and repelling the contradiction from it; this is because the science of the various hadiths is a great science with rules and foundations that only those with exceptional and profound linguistic, rhetoric, interpretation, Al-Hadith, jurisprudence and its origins can comprehend. Ibn Furak was an Imam and one of the Islamic figures in this category. Recently, there have been a lot of problematic issues in hadith texts that appear to be ambiguous and contradictory, and given the importance of the hadith problems, which eliminates the problem and contradiction from the hadith. It is worthwhile to highlight the methodology of scholars who have written in this field to be aware of their methods and scientific and doctrinal approaches. This research demonstrates the Imam’s efforts methodology, and the scientific value of his book, many scholars who spoke about names and characteristics who came after him were influenced by his approaches, like Imam al-Bayhaqi and others of al-Ash’ari school who paid a lot of attention to the names and characteristics, such as hand, eye, and intercourse, and exaggerated in interpretation. The modern reader should know these interpretations and the curriculums of the contemporaries. It is obvious from the methods of scholars in decoding ambiguities and problems in al-Hadith texts through scientific methods, so that the reader may distinguish the approach of Ahl al-Sunnah wal-Jamaa’ah from the approach of people of opinion and speech.